Morphological and Pigment Responses to Far-Red and Photosynthetically Active Radiation in an Olive Cultivar Suitable for Super-High-Density Orchards - Ladux, Federico J.; Gonzalez, Carina Veronica; Trentacoste, Eduardo Rafael; Searles, Peter Stoughton; Rousseaux, María Cecilia (MDPI, 2024)
Plant density is increasing in modern olive orchards to improve yields and facilitate mechanical harvesting. However, greater density can reduce light quantity and modify its quality. The objective was to evaluate plant morphology, biomass, and photosynthetic pigments under different red/far-red ratios and photosynthetically active radiation (PAR) combinations in an olive cultivar common to super-high-density orchards. In a greenhouse, young olive trees (cv. Arbequina) were exposed to low (L) or high (H) PAR with or without lateral FR supplementation (L+FR, L-FR, H+FR, H-FR) using neutral-density shade cloth and FR light-emitting diode (LED) modules. Total plant and individual organ biomass were much lower in plants under low PAR than under high PAR, with no response to +FR supplementation. In contrast, several plant morphological traits, such as main stem elongation, individual leaf area, and leaf angle, did respond to both low PAR and +FR. Total chlorophyll content decreased with +FR when PAR was low, but not when PAR was high (i.e., a significant FR*PAR interaction). When evaluating numerous plant traits together, a greater response to +FR under low PAR than under high PAR appeared to occur. These findings suggest that consideration of light quality in addition to quantity facilitates a fuller understanding of olive tree responses to a light environment. The +FR responses found here could lead to changes in hedgerow architecture and light distribution within the hedgerow.